The Impact of Board Oversight Functions on the Performance of Listed Companies in Nigeria - Ezekiel Oluwagbemiga Oyerogba; Muyiwa Ezekiel Alade; Patrick Esiemogie Idode; Isaiah Ogungbade Oluyinka (Journal of Accounting and Management Information Systems (JAMIS), 2017)
We ascertain the impact of board oversight functions on the financial performance of listed companies. The study covers the entire 186 companies listed on the Nigeria stock exchange for a period of five years between 2010 and 2014. Three aspect of board oversight function which includes the audit committee function, risk management committee function and remuneration/human capital committee function were considered in this study in line with the provision of (SEC) code of corporate governance and (OECD) code of corporate governance. Return on capital employed and earnings per share were used as the measures of firm financial performance. We conducted both descriptive and inferential statistics on a set of data extracted from the audited financial statement of the listed companies. The descriptive statistics include the mean, standard deviation, minimum and maximum value for each variable while the inferential statistics includes the univariate t- test and multivariate regression analysis. The findings of this study revealed that board oversight function have significant impact on the financial performance of listed companies in Nigeria. The significant relationship between the board oversight functions and financial performance reported in this study have been asserted in previous literature in Africa (Beltratti & Stulz, 2009) and Asia (Fahlenbrach & Stulz, 2009; Fernandes & Fich, 2009) which implies that this might be the global trend on the topic. Thus, the general hypothesis which predicts a significant relationship between board oversight function and firm financial performance cannot be rejected. Therefore, the recommendations emanating from this study is that concerted efforts should be put in place by the security and exchange commission to ensure strict compliance with regulations regarding the formation of audit committee and other oversight committees by the Nigerian listed companies.
Keywords: M41; 650; Board Oversight Functions; Audit Committee Functions; Risk Management Committee Functions; Remuneration Committee Functions; Return on Capital Employed; Earnings per Share